Antioxidative effects of thiazide diuretics in refractory hypertensive patientsA randomized crossover trial of chlortalidone and trichlo rmethiazide - Sat, Koichi; Dohi, Yasuaki; Kojima, Masayoshi; Takase, Hiroyuki; Suzuki, Shin; Ito, Shigenori (Arzneimittelforschung, 2010)
Some thiazide diuretics seem to exert antioxidant effects, which may be beneficial in the management of hypertension. Although many largescale clinical trial on hypertension have proved that thiazide diuretics confer significant reductions in stroke and cardiovascular events most of these trials preferentially used chlortalidone. Therefore, the difference in antioxidant effects between chlortalidone (CAS 77-36-1; 12.5 mg/day) and another thiazide diuretic, trichlormethiazide (CAS 133-67-5; 1 mg/day) was studied. Forty patients with refractory hypertension even after treatment with combination of a calcium channel blocker and an angiotensin II receptor blocke were randomly assigned to additionally receive either chlortalidone or trichlormethiazide for 6 months. Then, diuretic were switched in each patient and the were treated for another 6 months. Ambulatory blood pressure was monitored for 24 h and markers of inflammation (C-reactive protein) and oxidative stress (8-isoprostane, malondialdehyde-modified low-density lipoproteins) were measured before and after each treatment Addition of chlortalidone resulted in greater reduction of blood pressure (mean of 24 h; from 146.8 ± 18.0/83.8 ± 12.2 mmHg to 122 ± 18/72 ± 11 mmHg) than that of trichlormethiazide (134 ± 18/78 ± 11 mmHg, p < 0.001). The levels of C-reactive protein, malondialdehyde-modified low-density lipoproteins, and 8-isoprostane were lower after chlortalidone therapy than after trichlormethiazide therapy. These results suggest that chlortalidone is superior to trichlormethiazide in patients with essential hypertension.
Keywords: Chlortalidone; 24 h ambulatory blood; pressure monitoring; Oxidative stress; Refractory hypertension; Thiazide diuretic; Trichlormethiazide